Minturno (Lazio), Italien: Das Stadtzentrum - von Hesberg, Henner (e-Forschungsberichte des DAI, 2023)
The project focuses on a new documentation of formerly excavated remains at the site, which yet lack a reconstruction of the architectural structures as well as a complete recording. The approach will help to develop a new interpretation of the main buildings, i.e. the two temples at the forum, the forum with the basilica and the theatre. In many cases different phases can be distinguished. A particular focus has been placed on water management and water architecture in the town.